Old black Joe - Foster, Stephen Collins, 1826-1864 (Lyricist); Foster, Stephen Collins, 1826-1864 (Composer) (Sims Song Slide Corporation (Kirksville, Mo.), 1853)
Songs; Scores; Glass lantern slide depicting score of "Old Black Joe."